The Characteristics of Four-Tier Diagnostic Test: Classical Test Theory Perspective - Prabowo, Anggit; Herman, Tatang; Fatimah, Siti (Universitas Ahmad Dahlan, 2023)
This study is part of developing a four-tier online diagnostic test for geometry in junior high schools in Indonesia. After wrote the items and validated by experts, items were tested on 249 students in Yogyakarta, one of the Special Regions in Indonesia. This study aims to identify the characteristics of a four-tier online diagnostic test, from a classical test theory (CTT) perspective. This test contains 20 items of four-tier multiple choice with four options. The students’ responses were analyzed using Item and Test Analysis (ITEMAN) package. Item difficulty index, discriminant index, and reliability coefficient were three attributes analyzed. The average of item difficulty index is 0.384 (moderate category). The average item discriminant index is 0.513 (good category). The estimation of the reliability coefficient using the Cronbach-Alpha formula is 0.706 (good category).